Implementasi Virtual Reality Pada Game Edukasi Penyeberangan Jalan (PELAN) - Fathurrahman Annafabi; Muhammad Aminul Akbar; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Educational games have been widely used as a learning media. Educational Games are designed to help the learning process and provide experience to the players, and are proven to be effective to use as a learning media. A game called PELAN has been created to help children learning to cross the road on a computer program, where the use of Augmented Reality in games has a positive effect on children's learning. With the advent of Virtual Reality (VR) technology, which is a virtual environment generated by the computers, users can enter into the reality that has been created, so that the addition of VR with Google Cardboard in the game can add to the gaming experience and indirectly add to the learning process provided from playing the game. The research was conducted to develop the PELAN game using VR technology with the aim of increasing the experience given to users that played it and so that it indirectly improves the learning performance provided by the game. The implementation of the game uses the Big Bang method, a software development model that has the flexibility and ease of change design that is expected to help answers the needs of the research. The game that has been made has been tested for its functionality using Black Box Testing, where each functionality in the study is declared valid, and the Game Experience Questionnaire (GEQ) questionnaire is held, where the average score of the positive component is approximately three, which is good , and the average negative effect value is less than 2 which means less than enough, along with the comparison if using kinect as a game controller.